Accumulation of commonly used agricultural herbicides in coral reef organisms from iSimangaliso Wetland Park, South Africa - Tyohemba, Raymond L.; Humphries, Marc S.; Schleyer, Michael H.; Porter, Sean N. (Environmental pollution (1987), 2022)
Coral reefs are amongst the most biodiverse ecosystems on earth, but are significantly impacted by agricultural runoff. Despite herbicides being commonly detected in coastal waters, the possibility of herbicide accumulation in coral reef species has largely been overlooked. We investigate the accumulation of several herbicides in five species of coral reef invertebrates collected from ten sites along the Maputaland coast, South Africa. Multiple herbicide residues were detected in 95% of the samples, with total average concentrations across sites ranging between 25.2 ng g−1 to 51.3 ng g−1 dw. Acetochlor, alachlor and hexazinone were the predominant herbicides detected at all sites, with atrazine and simazine detected less frequently. Significant interactive effects were detected between sites nested in reef complex crossed with species, based on multiple and total herbicide concentrations. In general, multivariate herbicide concentrations varied significantly between species within and across most sites. Contrastingly, the concentrations of the different herbicides and that of total herbicide did not differ between conspecifics at most sites nested in their respective reef complexes. On average, highest total herbicide concentrations were measured in soft coral (Sarcophyton glaucum; 90.4 ± 60 ng g−1 and Sinularia gravis; 42.7 ± 25 ng g−1) and sponge (Theonela swinhoei; 39.0 ± 40 ng g−1) species, while significantly lower concentrations were detected in hard corals (Echinopora hirsutissima; 10.5 ± 5.9 ng g−1 and Acropora austera; 5.20 ± 4.5 ng g−1) at most sites. Agricultural runoff entering the ocean via the uMfolozi-St Lucia Estuary and Maputo Bay are likely sources of herbicide contamination to coral reefs in the region. There is an urgent need to assess the long-term effects of herbicide exposure on coral reef communities. [Display omitted] •Herbicides detected in coral reef organisms from a global biodiversity hotspot.•Herbicide prevalence related to fluvial inputs from agricultural areas.•Highlights potential threats of agricultural runoff to coral reef ecosystems globally.